2017
DOI: 10.18466/cbayarfbe.302657
|View full text |Cite
|
Sign up to set email alerts
|

Acid Dissociation Constants of 5,5-Diphenylpyrrolidine N-Aroylthioureas and Stability Constants of their Pt(II) and Ni(II) Complexes in Acetonitrile-Water Hydroorganic Solvent

Abstract: In this study, acid dissociation constants of 5,5-diphenylpyrrolidine N-aroylthiourea derivatives, exhibiting anti(myco)bacterial activity, were determined by potentiometric titration in 30% (v/v) acetonitrile-water hydroorganic solventat 25 ± 0.1 °C, at an ionic background of 0.1 mol / L of NaCl using the HYPERQUAD computer program. Three acid dissociation constants were determined for each compound 1a-e and we suggest that these acid dissociation constants are related to the carboxyl, enol and enthiol groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In studies on the determination of pKa values of acyl thiourea derivative compounds, potentiometrically, one pKa value in the range of 9.82-10.19 for each of the benzoylthiourea derivatives in 75:25 (v/v) dioxane-water was reported by Schröder et al (65). In addition, for each 5,5-diphenylpyrrolidine Naroylthiourea compound in 30:70 (v/v) acetonitrilewater, potentiometrically two pKa values, which were in the range of 6.96±0.03 to 7.84±0.04 associated with enol and in the range of 8.29±0.02 to 9.94±0.08 associated with enthiol groups, were reported (66). In other study, for each pyrrolidine Naroylthioureas in 25:75 (v/v) DMSO-water, potentiometrically two pKa values, which were in the range of 5.85±0.08 to 6.06±0.06 associated with enol, in the range of 8.37±0.05 to 8.87±0.05 associated with enthiol groups, and in the range of 10.11±0.03 to 11.62±0.03 associated with NH, were reported (67).…”
Section: Acid Dissociation Constantsmentioning
confidence: 75%
“…In studies on the determination of pKa values of acyl thiourea derivative compounds, potentiometrically, one pKa value in the range of 9.82-10.19 for each of the benzoylthiourea derivatives in 75:25 (v/v) dioxane-water was reported by Schröder et al (65). In addition, for each 5,5-diphenylpyrrolidine Naroylthiourea compound in 30:70 (v/v) acetonitrilewater, potentiometrically two pKa values, which were in the range of 6.96±0.03 to 7.84±0.04 associated with enol and in the range of 8.29±0.02 to 9.94±0.08 associated with enthiol groups, were reported (66). In other study, for each pyrrolidine Naroylthioureas in 25:75 (v/v) DMSO-water, potentiometrically two pKa values, which were in the range of 5.85±0.08 to 6.06±0.06 associated with enol, in the range of 8.37±0.05 to 8.87±0.05 associated with enthiol groups, and in the range of 10.11±0.03 to 11.62±0.03 associated with NH, were reported (67).…”
Section: Acid Dissociation Constantsmentioning
confidence: 75%
“…As a continuation of our previous studies (5,41), this study reports the synthesis and determination of acid dissociation constants of 5,5-diphenylpyrrolidine N-aroylthiourea derivatives in dimethyl sulfoxide-water hydro-organic solvent.…”
Section: Introductionmentioning
confidence: 85%
“…The pKa values of (2S, 4S)-5,5-diphenylpyrrolidine N-aroylthioureas 3a-d were determined potentiometrically in a 25% (v/v) DMSO-water hydro-organic solvent system at 25.0±0.1 °C ( for each N-aroylthiourea compound in a 50% (v/v) dioxane-water mixture. The previous study [41] reported three potentiometrically different pKa values for each (2S, 4S)-5,5diphenylpyrrolidine N-aroylthiourea compound in the 30% (v/v) acetonitrile-water hydroorganic solvent system. The present study suggested that the pKa1 values in the range of 3.49±0.07 to 5.19±0.04 were related to carboxyl, the pKa2 values in the range of 6.96±0.03 to 7.84±0.04 were related to enol, and the pKa3 values in the range of 8.29±0.02 to 9.94±0.08 were related to enthiol groups.…”
Section: Acid Dissociation Constantsmentioning
confidence: 99%
“…Aspartic acid (asp) and glutamic acid (glu), being acidic amino acids, play significant roles in the enzyme active centers, along with in sustaining the solubility and ionic character of proteins. Many studies in the literature have focused on experimentally and computationally determining the protonation constant of ligands and their stability constants of the complexes formed with metal ions (6)(7)(8). Recently, we have reported that (1:1) and (1:1:1) palladium(II) and copper(II) complexes of amino acids, 1,10-phenanthroline, and derivatives in aqueous solution (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%